Mitigation of late cardiovascular effects of oxygen ion radiation by γ-tocotrienol in a mouse model. (November 2021) - Nemec-Bakk, Ashley S.; Sridharan, Vijayalakshmi; Landes, Reid D.; Singh, Preeti; Cao, Maohua; Seawright, John W.; Liu, Xingui; Zheng, Guangrong; Dominic, Paari; Pathak, Rupak; Boerma, Marjan
Abstract: Purpose: While there is concern about degenerative tissue effects of exposure to space radiation during deep-space missions, there are no pharmacological countermeasures against these adverse effects. γ-Tocotrienol (GT3) is a natural form of vitamin E that has anti-oxidant properties, modifies cholesterol metabolism, and has anti-inflammatory and endothelial cell protective properties. The purpose of this study was to test whether GT3 could mitigate cardiovascular effects of oxygen ion ( 16 O) irradiation in a mouse model. Materials and methods: Male C57BL/6 J mice were exposed to whole-body 16 O (600 MeV/n) irradiation (0.26–0.33 Gy/min) at doses of 0 or 0.25 Gy at 6 months of age and were followed up to 9 months after irradiation. Animals were administered GT3 (50 mg/kg/day s.c.) or vehicle, on Monday – Friday starting on day 3 after irradiation for a total of 16 administrations. Ultrasonography was used to measure in vivo cardiac function and blood flow parameters. Cardiac tissue remodeling and inflammatory infiltration were assessed with histology and immunoblot analysis at 2 weeks, 3 and 9 months after radiation. Results: GT3 mitigated the effects of 16 O radiation on cardiac function, the expression of a collagen type III peptide, and markers of mast cells, T-cells and monocytes/macrophages in the left ventricle. Conclusions: GT3 may be a potential countermeasure against late degenerative tissue effects of high-linear energy transfer radiation in the heart.